2019
DOI: 10.7202/1060030ar
|View full text |Cite
|
Sign up to set email alerts
|

Does Corporate Social Responsibility Reduce Earnings Management? The Moderating Role of Corporate Governance and Ownership

Abstract: The purpose of this paper is to investigate the relationship between corporate social responsibility and earnings management and the moderating effect of corporate governance and ownership structure on this relationship. Using panel data for a sample of French listed companies between 2010 and 2013, we find that CSR engagementconstrain earnings management practices suggesting that managers would comply with the ethical requirements and satisfy stakeholders’ interests. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 95 publications
3
18
0
Order By: Relevance
“…Previous studies have disclosed that the relationship between corporate social responsibility and earnings management was positive and significant (Habbash & Haddad, 2019;Jiang et al, 2013;López-González et al, 2019;Shafai et al, 2018). In contrast, Ajina et al (2019); Ben Amar and Chakroun ( 2018 Scholtens and Kang (2013) found that corporate social responsibility had a significant adverse effect on earnings management. Therefore, the researchers formulated the following hypothesis: H 1 : Corporate social responsibility disclosure has a significant negative effect on earnings management Further, earnings management is an action intentionally carried out by management in presenting misguided information about company performance so that shareholders change their decision (Schipper, 1989).…”
Section: Hypothesesmentioning
confidence: 95%
See 2 more Smart Citations
“…Previous studies have disclosed that the relationship between corporate social responsibility and earnings management was positive and significant (Habbash & Haddad, 2019;Jiang et al, 2013;López-González et al, 2019;Shafai et al, 2018). In contrast, Ajina et al (2019); Ben Amar and Chakroun ( 2018 Scholtens and Kang (2013) found that corporate social responsibility had a significant adverse effect on earnings management. Therefore, the researchers formulated the following hypothesis: H 1 : Corporate social responsibility disclosure has a significant negative effect on earnings management Further, earnings management is an action intentionally carried out by management in presenting misguided information about company performance so that shareholders change their decision (Schipper, 1989).…”
Section: Hypothesesmentioning
confidence: 95%
“…In addition, management as a party with more information about the company can manipulate information provided to shareholders so that shareholders are wrong in making decisions (Mayapada, 2018). However, management must take these opportunistic actions carefully so that management is not acted upon by shareholders, including using corporate social responsibility to mislead shareholders of the real value of the firm and its real performance (Ajina et al, 2019).…”
Section: Agency Theory and Stakeholder Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The mixed results can be attributed to different contexts and, therefore, different studied legal frameworks and the different earnings management measures used. From a review of published papers between 2008 and 2016 by Rahman and Chowdhury (2020), we noticed that most studies use AEM as an EM measure (Almahrog et al, 2018;Amar & Chakroun, 2018;López-González et al, 2019;Ajina et al, 2019). Generally, REMrelated studies jointly deal with AEM.…”
Section: Theoretical Framework and Research Hypotheses Csr Performanc...mentioning
confidence: 99%
“…Prior empirical research works provide evidence on the difference between REM and AEM activities in their relationship with CSR (Bozzolan, Fabrizi, Mallin, & Michelon, 2015;García-Sánchez & García-Meca, 2017;Jordaan, De Klerk, & De Villiers, 2018;Kim, Udawatte, & Yin, 2019). First, while prior studies on the French context focused on AEM (Amar & Chakroun, 2018;Ajina, Lakhal, & Ayed, 2019), we aimed to define the effect of CSR on REM activities. Second, we emphasized the moderating role of board gender diversity in the CSR-REM relationship in the French context.…”
Section: Introductionmentioning
confidence: 99%